Proceedings of the 2015 Chinese Intelligent Systems Conference Volume 2 - Jia, Yingmin; Du, Junping; Li, Hongbo; Zhang, Weicun; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
This book presents selected research papers from the 2015 Chinese Intelligent Systems Conference (CISC'15), held in Yangzhou, China. The topics covered include multi-agent systems, evolutionary computation, artificial intelligence, complex systems, computation intelligence and soft computing, intelligent control, advanced control technology, robotics and applications, intelligent information processing, iterative learning control, and machine learning. Engineers and researchers from academia, industry and the government can gain valuable insights into solutions combining ideas from multiple disciplines in the field of intelligent systems.
Containment Control of Second-Order Multi-Agent Systems with Jointly-Connected Topologies and Varying Delays -- An Extend Set-Membership Filter for state estimation in Power Systems -- Sensor Fault Detection of double tank Control System Based on Principal Component Analysis -- An Activity Recognition Algorithm Based on Multi-feature Fuzzy Cluster -- Application of fractal on the fluids.
Keywords: Computational intelligence; Artificial intelligence; Control engineering; Robotics; Automation; Computational Intelligence; Artificial Intelligence; Control, Robotics, Automation